Determinants of Failure to Thrive among Children Aged 6-24 Months - Utami, Shinta; Laila, Eka Fauzia (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Failure to thrive is still a common problem among children, especially in developing countries, and it is one of the risk factors for stunting. Factors that contribute to failure to thrive are medical conditions, nutrition, eating skills, and psychosocial characteristics. This study was conducted to determine the prevalence of growth failure in children and the factors that influence failure to thrive in children aged 6-24 months who live in the working area of Cisaat Health Center.Method: This research uses a cross-sectional design to examine 125 respondents. The data were acquired from semi-quantitative food frequency questionnaires and were analyzed using logistic regression. Results: The prevalence of failure to thrive was 38.4% (48 children). The results of the multivariate analysis showed that children's age influences failure to thrive. In this case, the age of 6-15 months is the most vulnerable period (OR=3.4; 1.46-8.04), low education of mothers (OR=6.52; 2.77-15.30), sub-standard family income (OR=3.6; 1.67-7.78), low energy intake (OR=5.08; 2.33-11.10), low iron intake (OR=4.14; 1.88-9.129), and low zinc intake (OR=4.07; 1.89-8.75). The most dominant factor for failure to thrive in children is the mother's education level. Health personnel should routinely detect the incidence of failure to thrive health personnel so that the problem of failure to thrive in children can be identified early.